Practical Intelligence Teaching Approach: Effects on Social Competence and Problem-solving Ability in Biology - Mercado, Celeste T (Asian Journal of Multidisciplinary Studies, 2017)
The study focused on Practical Intelligence (PI) Teaching Approach as an intervention in high school biology. Specifically, it sought to determine the effects of the approach on students’ practical intelligence in terms of problem-solving skills and social competence. It also tried to establish the relationship between social competence and problem-solving skills. Two sections of second year biology students in a private school in Metro Manila were taught by the researcher using the PI Teaching Approach and the conventional approach, respectively for eight weeks during the second quarter of School Year 2008-2009. Social competence was measured using scenarios which called for socially-oriented responses. Tests measuring problem-solving skills included stressful problem situations that students encounter in their environment. Findings reveal that the PI Teaching Approach was effective in developing social competence particularly the empathy component and social attributes specifically individual and peer attributes. It is noted, however, that there is no significant difference between the experimental and conventional groups’ problem-solving skills, though the experimental group performed much better than the control group in some items in the Critical Incidents Test (CIT) and Real World Test (RWT). Though there was no positive significant relationship between problem-solving ability and social competence, there were positive significant relationships between the CIT and some of the components of social competence, namely, clarity and authenticity. There was also a positive relationship between the RWT and all the components of social competence which include presence, authenticity, clarity and empathy.